2006
DOI: 10.5232/ricyde2006.00401
|View full text |Cite
|
Sign up to set email alerts
|

Los factores ambientales y su influencia en los patrones de actividad física en adolescentes. (The environmental factors and their influence in the patterns of physical activity in adolescents.)

Abstract: Los factores ambientales y su influencia en los patrones de Los factores ambientales y su influencia en los patrones de actividad física en adolescentes. actividad física en adolescentes.The environmental factors and their influence in the The environmental factors and their influence in the patterns of physical activity in adolescents. patterns of physical activity in adolescents.Zaragoza Casterad, Javier La mayoría de estudios demuestran; a) un descenso de la actividad física (AF) que coincide con la adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
2
5
1
Order By: Relevance
“…Based on the suggestions of others (Baranowski & deMoor, 2000;Jago et al, 2005;Plasqui & Westerterp, 2004;Rowlands & Hughes, 2006;Trost et al, 2000), we also examined when Spanish adolescents were active and inactive. In line with previous research with Spanish samples (Cantera-Garde & Devı ´s-Devı ´s, 2000; Zaragoza et al, 2006), our sample showed higher activity during weekends than during weekdays. These findings are not necessarily compatible with those of studies from other countries.…”
Section: Seasonal and Weekday/weekend Variations In Physical Activitysupporting
confidence: 93%
See 3 more Smart Citations
“…Based on the suggestions of others (Baranowski & deMoor, 2000;Jago et al, 2005;Plasqui & Westerterp, 2004;Rowlands & Hughes, 2006;Trost et al, 2000), we also examined when Spanish adolescents were active and inactive. In line with previous research with Spanish samples (Cantera-Garde & Devı ´s-Devı ´s, 2000; Zaragoza et al, 2006), our sample showed higher activity during weekends than during weekdays. These findings are not necessarily compatible with those of studies from other countries.…”
Section: Seasonal and Weekday/weekend Variations In Physical Activitysupporting
confidence: 93%
“…Cantera‐Garde and Devís‐Devís (2000) reported a moderately high energy expenditure (38.70 kcal·kg −1 ·day −1 , s =4.40), with 42.8% of adolescents being “inactive” or “very inactive”. Similarly, adolescents from two cities in Northern Spain (Zaragoza et al ., 2006) displayed lower energy expenditure than the adolescents in our study (37.66 kcal·kg −1 ·day −1 , s =2.95 and 39.17 kcal·kg −1 ·day −1 , s =5.10, respectively), with 47% of adolescents being “inactive” or “very inactive” in the former and 39% in the latter. Studies from other countries using the same instrument also showed lower energy expenditures than the present study.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The PA practice in our study shows that women do more moderate PA than men, as stated by [71]. However, men in general are more active in the moderate-vigorous PA [72,73].…”
Section: Discussionsupporting
confidence: 69%